2018
DOI: 10.3390/app8030362
|View full text |Cite|
|
Sign up to set email alerts
|

Orbital Angular Momentum Generation and Detection by Geometric-Phase Based Metasurfaces

Abstract: Abstract:We present a comprehensive review on the geometric-phase based metasurfaces for orbital angular momentum (OAM) generation and detection. These metasurfaces manipulate the electromagnetic (EM) wave by introducing abrupt phase change, which is strongly dependent on the polarization state of incident EM wave and can be interpreted by geometric phase. Hence, the conventional bulk devices that based on the accumulated phase change along the optical path can be avoided.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 103 publications
1
46
0
Order By: Relevance
“…A high degree of control over the different approaches for generation and manipulation of vortex beams carrying OAM has been achieved in the last couple of decades, at an unparalleled rate. Similarly impressive are the potential avenues of applications ranging from optical microscopy, microengineering, to classical and quantum communications, among other exciting research directions [1,2,3,4,5]. Geometric phase elements [42], also known as q-plates, can couple SAM and OAM by converting a given state of circular polarization into its opposite, while imprinting an azimuthal phase profile with a fixed topological charge.…”
Section: Oam Modes and Topological Chargementioning
confidence: 99%
See 1 more Smart Citation
“…A high degree of control over the different approaches for generation and manipulation of vortex beams carrying OAM has been achieved in the last couple of decades, at an unparalleled rate. Similarly impressive are the potential avenues of applications ranging from optical microscopy, microengineering, to classical and quantum communications, among other exciting research directions [1,2,3,4,5]. Geometric phase elements [42], also known as q-plates, can couple SAM and OAM by converting a given state of circular polarization into its opposite, while imprinting an azimuthal phase profile with a fixed topological charge.…”
Section: Oam Modes and Topological Chargementioning
confidence: 99%
“…2D metamaterials, also known as metasurfaces [2,3,4], is an emerging interdisciplinary field which promotes the of use alternative approaches for light arXiv:1904.02647v2 [physics.optics] 25 Jul 2019 engineering based on subwavelength-thick metasurfaces built upon metaatoms, with spatially varying compositions. They exhibit remarkable properties in maneuvering light at a 2D interphase.…”
Section: Introductionmentioning
confidence: 99%
“…The key point to produce OAM waves by M. L. N. Chen using geometric-phase based metasurface is to make the local phase change equal to e ilφ . Various prototypes of scatterers on these metasurfaces have been proposed for OAM generation, such as split-ring resonators [23,24], L-shaped and elliptical nano antennas [25,26]. However, the performance could be degraded due to the unwanted coupling among scatterers and high-order diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by keeping the local period small enough, no high-order diffraction exists. Regarding vortex beams carrying arbitrary orders of OAM, in conventional metasurfaces, discrete scatterers are placed at specific locations with pre-designed orientations [23][24][25][26]. However, the discontinuity and aperiodicity induced by the discrete scatterers will distort the near-field pattern [27] and lower the efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We, the authors, wish to make the following corrections to our paper [1]. We found that the literature we listed on page 2 has a mistake:…”
mentioning
confidence: 99%